1993
DOI: 10.1063/1.354009
|View full text |Cite
|
Sign up to set email alerts
|

Defects in electron irradiated GaInP

Abstract: We present a characterization of the defects created by electron irradiation at room temperature in n-type GaInP. Four electron traps, labeled E1–E4, and no hole traps have been detected using deep level transient spectroscopy in the temperature range 4–400 K. The corresponding energy levels and barriers associated with electron capture have been measured. The introduction rates, ranging from 4×10−3 to 0.4 cm−1, indicate that these defects are probably not primary defects but complexes resulting from the inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(13 citation statements)
references
References 12 publications
1
12
0
Order By: Relevance
“…This is the same trap, labeled N3, which we observed in a previous paper, 4 the somewhat larger capture cross section here is a result of newer measurements on several different samples. The trap is also very similar to the trap seen previously in InGaP by Blood et al 5 It is also similar to the radiation-induced defect seen by Zaidi et al 6 However, Zaidi reported a large capture barrier ͑0.175 eV͒ for that defect while we found no significant barrier for the N3 defect. After thermal annealing at temperatures of up to 500 K, no changes in the concentration of the defect were seen.…”
Section: Methodssupporting
confidence: 91%
See 1 more Smart Citation
“…This is the same trap, labeled N3, which we observed in a previous paper, 4 the somewhat larger capture cross section here is a result of newer measurements on several different samples. The trap is also very similar to the trap seen previously in InGaP by Blood et al 5 It is also similar to the radiation-induced defect seen by Zaidi et al 6 However, Zaidi reported a large capture barrier ͑0.175 eV͒ for that defect while we found no significant barrier for the N3 defect. After thermal annealing at temperatures of up to 500 K, no changes in the concentration of the defect were seen.…”
Section: Methodssupporting
confidence: 91%
“…4 There, DLTS and time resolved photoluminescence measurements were combined to show that the reduction of N3 concentration following rapid thermal annealing could explain the lower threshold currents observed in annealed InGaP quantum well lasers. Romero et al 8 have also reported on the recombination efficiency of a midgap level created by proton irradiation, which was identified with the electron irradiation induced trap measured by Zaidi et al 6 While neither of these works reported any signs of REA for the midgap trap, the process is very common among radiation induced defects. For example, five of the six radiation induced levels in GaAs are subject to REA, while all six deep levels investigated in irradiated GaP exhibit REA.…”
Section: Discussionmentioning
confidence: 86%
“…The sample given the highest dose was rendered untestable, though C-V measurements showed a large drop in net doping density. In 1 MeV electron irradiated GaInP, Zaidi reported four peaks, 9 the deepest of which is very close to the midgap defect observed in these samples. The other defects in that work had lower introduction rates and may be obscured beneath the very broad peaks seen in our samples.…”
Section: Experimental Methods: Sample Preparation and Dlts Measurmentioning
confidence: 89%
“…Irradiation damage on GaAs has already been extensively studied, including the determination of the range of protons and helium ions [8], irradiation induced changes of index of refraction [9], carrier compensation [10], and annealing effects [11], to give some examples. However, for InGaP material we found only a few reports of irradiation experiments, mostly related to the electrical parameters of the devices [12,13] and few about defects in the material [14,15]. Although for InP and GaP compounds some works show differences between experimental results and simulations regarding the penetration of protons [16], experiments on ion ranges for InGaP have not been reported yet.…”
Section: Introductionmentioning
confidence: 82%